RANCANG BANGUN SISTEM INFORMASI PREVENTIVE MAINTENANCE BERBASIS WEB PADA PERUSAHAAN MANUFAKTUR - Ansyah, Hari; Saragih, Saut Pintubipar (LPPM Universitas Putera Batam, 2021)
In order to improve the best service for its customers, PT Multi Engineering Perkasa sends a maintenance team and implements a preventive maintenance system on each machine distributed to their customers during the warranty period. Problems faced by maintenance such as delays in determining production machine repair schedules, machine repair job checklist data collection, and insufficient information facilities needed by PT Multi Engineering Perkasa regarding history of damage or checking on production machines which are still done manually, using hardcopy. This research uses the Waterfall model of Software Development Life Cycle (SDLC) development method. The waterfall model has five stages, namely analysis, design, coding, testing and maintenance. This application is created using the programming language PHP, HTML and MySQL as a database. And as a result, the web-based preventive maintenance information system can help maintenance in carrying out preventive maintenance data, especially helping in terms of information so that it can be used as a decision-making material, as well as on the part of the customer can quickly see the repair / preventive maintenance report data when needed.